When trauma turns outward: Externalising mental health difficulties as a mediating pathway to radicalisation - Esheref Haxhiu; Gino Casale; Eva Lembke; Friedrich Linderkamp (Educational and Child Psychology, 2026)
Aim: This study examined whether the association between trauma and adolescents’ radicalisation intentions is mediated by externalising rather than internalising mental health difficulties. Method/Rationale: Data were analysed from 280 secondary school students in Germany aged 12 to 19 years, including 16% with a refugee background. Participants completed self-report measures of traumatic experiences, post-traumatic stress symptoms, emotional and behavioural difficulties, and radicalisation intentions. Mediation analyses tested traumatic experiences and posttraumatic stress symptoms as predictors, with externalising and internalising difficulties as separate mediators and radicalisation intentions as the outcome variable. Findings: Traumatic experiences were indirectly associated with stronger radicalisation intentions through externalising difficulties. Internalising difficulties did not mediate this association. A similar pattern emerged for post-traumatic stress symptoms, which were indirectly associated with radicalisation intentions through externalising difficulties but not through internalising difficulties. Limitations: The cross-sectional design limits causal interpretation, and all variables were assessed through self-report. The sample was drawn from one region of Germany, which may limit generalisability. Conclusions: The findings suggest that trauma may increase adolescents’ vulnerability to radicalisation primarily through outwardly directed behavioural dysregulation rather than internal emotional distress. This highlights the importance of trauma-informed, school-based identification and support for externalising difficulties.